A mesoscale assessment of sinking oil during dispersant treatment. (1st November 2022) - Cao, Ruichen; Chen, Haibo; Li, Haoshuai; Fu, Hongrui; Wang, Yuzhe; Bao, Mutai; Tuo, Wenhao; Lv, Xianqing
Abstract: Although much is known about the sinking of oil in marine environments, considerable gaps persist when modelling the oil sinking process. Scientific models are still needed to characterise the sunken oil and understand its mechanisms under various environmental conditions. In this study, a model is developed to investigate the sinking characteristics of oil with and without the effect of dispersant treatment. By coupling a Lagrangian particle module, a wave action module, a weathering module, and a droplet size variation module, the model is tested by experimental data obtained from a mesoscale wave tank (32 m × 0.8 m × 2 m). The influence of dispersant on the formation of small ( d  <  d 50 ) and large droplets ( d  ≥  d 50 ) in the experimental oil is identified, and the contribution of dispersants to the effective sinking of oil is given by model simulation. The model results show that the addition of dispersants can significantly increase the amount of sunken oil, with the effect of dispersants being enhanced by wave action. The model establishes mechanisms to explain oil sinking characteristics, clarifying oil spill behaviour and providing new ideas for the dispersant treatment of sinking oil. Highlights: An oil sinking model is developed and validated by experimental data. Submergence characteristics of three experimental oils are successfully simulated. Oil sinking mechanisms are established and confirmed by experimental data. Contribution of dispersant treatment to effective oil sinking is configured.